2014
DOI: 10.1590/s1415-43662014000300006
|View full text |Cite
|
Sign up to set email alerts
|

Propriedades físicas dos grãos de amendoim durante a secagem

Abstract: R E S U M OObjetivou-se, com o presente trabalho, avaliar o efeito da secagem sobre as características físicas dos grãos de amendoim. Foram utilizados grãos de amendoim com teor inicial de água de aproximadamente 0,56 decimal (base seca) e submetidos à secagem com temperatura de 40 ºC. Foram determinadas as propriedades físicas: massa específica aparente, massa específica unitária, porosidade intergranular, massa de mil grãos, esfericidade, circularidade, área projetada, área superficial e a relação superfície… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

7
23
1
19

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 41 publications
(50 citation statements)
references
References 18 publications
7
23
1
19
Order By: Relevance
“…Thus, the true density of safflower grains showed a trend similar to that of the bulk density. A similar trend to that of the present study for the true density has also been found for other species, such as for seeds of cucurbits (Milani et al, 2007), jatropha (Siqueira et al, 2012a), grains of pistachio and peanut (Araujo et al, 2014).…”
Section: Resultssupporting
confidence: 91%
See 2 more Smart Citations
“…Thus, the true density of safflower grains showed a trend similar to that of the bulk density. A similar trend to that of the present study for the true density has also been found for other species, such as for seeds of cucurbits (Milani et al, 2007), jatropha (Siqueira et al, 2012a), grains of pistachio and peanut (Araujo et al, 2014).…”
Section: Resultssupporting
confidence: 91%
“…A similar trend for the sphericity during the drying has also been reported for other species, such as peanut grains (Araujo et al, 2014), jatropha fruits (Siqueira et al, 2012b) and castor bean fruits (Goneli et al, 2011). The circularity and sphericity of safflower grains showed values below 70% and cannot be classified as either circular or spherical.…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…Araujo et al (2014) affirmed that this phenomenon occurs due to the reduction of the characteristic dimensions of the product during the desorption process, which contributes to the shrinking of the beans and, consequently, to the reduction of the projected area.…”
Section: Resultsmentioning
confidence: 87%
“…Araujo et al (2014) assessed the physical properties of peanut grains at different moisture contents and observed a reduction in the volume of the grains. This reduction in the volume of grains is related to volume contraction during the drying process due to the removal of water.…”
Section: Resultsmentioning
confidence: 99%